Penggunaan Power of Ethernet untuk Mengalirkan Arus Listrik ke Hardware yang Terhubung dengan Kabel UTP - Muhammad Safri Lubis; Mahdi Azis; Franheit Sangapta (Jurnal Rekayasa Elektrika, 2012)
Development of a local area network (LAN) needs a network cable such as UTP twisted pair especially for connecting hardware like personal computer with CCTV. The connection should be on the basis of IP address which is connected with switch, and then the data eventually is sent to server. Generally, in the field, a hardware network has two main connection; first, connections to electricity for switching on the software by using an electricity cable which is suitable to the need of electrical capacity; second, connection to UTP twisted network for sending the data to the server. This process can be simplified by using network cable both for sending the data to server and for electrical pathway. Some pairs of network cable which are not used for sending data to server can be occupied to convey electrical wave to switch on and to operate the hardware. In order to use network cable for multiple purposes, it needs electrical configuration such as power of ethernet (PoE). The PoE is a system to utilize the UTP twisted pair cable to transmit unoccupied power for electrical pathway so that it can increase the efficiency of system.